The skin of the film : intercultural cinema, embodiment, and the senses - Marks, Laura U. (Durham : Duke University Press, 2000)
- The memory of images ##- The memory of things ##- The memory of touch ##- The memory of the senses ##- Conclusion: The portable sensorium.
Onderzoek KASK (1KA-OFVR)
boek